Hubungan Pengetahuan, Sikap, Dan Peran Tenaga Kesehatan Terhadap Pemeriksaan Tripel Eliminasi Pada Ibu Hamil Di Puskesmas Satu Ulu Palembang Tahun 2023 - Sari, Puput Nopitri Agustri; Sari, Erma Puspita; Anggraini, Arie (Universitas Muhammadiyah Klaten, 2024)
According to WHO data, pregnant women are one of the populations at risk of contracting the Human Immunodeficiency Virus, Syphilis and Hepatitis B. The risk of transmission from mother to child for HIV/AIDS is 20% -45%, for syphilis is 69-80%. , and for Hepatitis B is more than 90%. One of the efforts to achieve better health for women is through the Triple Elimination examination, a program aimed at achieving and maintaining mother-to-child elimination of HIV/AIDS, Hepatitis B, and Syphilis. The aim of the researchers was to determine the relationship between knowledge, attitudes, and the role of health workers on the triple elimination examination of pregnant women at the Satu Ulu Health Center. Analytical Survey Design with a Cross Sectional approach. The population in this study were all pregnant women who made their first visit to the Satu Ulu Health Center, totaling 40 people. The sampling technique in this study used Accidental Sampling. The data collection technique in this study was to use primary data by using questionnaires. Data analysis used univariate analysis and bivariate analysis using the Chi Square test. The results of univariate analysis revealed that from 40 respondents who carried out the Triple Elimination examination in pregnant women, there were 34 respondents (85.0%), respondents with good knowledge were 35 respondents (87.5%), respondents with a positive attitude were 34 respondents (85%), respondents 35 respondents (87.5%) received the role of good health workers. The results of the bivariate analysis found that there was a relationship between knowledge (p value = 0.018), attitude (p value = 0.033) and the role of health workers (p value = 0.018) towards the Triple Elimination examination in pregnant women at Satu Ulu Health Center. The conclusion is that there is a relationship between knowledge, attitudes, and the role of health workers towards the Triple Elimination examination of pregnant women at Satu Ulu Health Center. It is hoped that the results of this study can increase information for pregnant women about the importance of the Triple Elimination examination so that they can prevent disease transmission (HIV, Syphilis, Hepatitis B) from mother to child.